Radiation‐Induced RhoGDIβ Cleavage Leads to Perturbation of Cell Polarity: A Possible Link to Cancer Spreading. Issue 11 (14th March 2016) - Fujiwara, Mamoru; Okamoto, Mayumi; Hori, Masato; Suga, Hiroshi; Jikihara, Hiroshi; Sugihara, Yuka; Shimamoto, Fumio; Mori, Toshio; Nakaoji, Koichi; Hamada, Kazuhiko; Ota, Takahide; Wiedemuth, Ralf; et al.
Abstract : The equilibrium between proliferation and apoptosis is tightly balanced to maintain tissue homeostasis in normal tissues and even in tumors. Achieving and maintaining such a balance is important for cancer regrowth and spreading after cytotoxic treatments. Caspase‐3 activation and tumor cell death following anticancer therapy as well as accompanying cell death pathways are well characterized, but their association to homeostasis of cancerous tissue and tumor progression remains poorly understood. Here we proposed a novel mechanism of cancer spreading induced by caspase‐3. RhoGDIβ, known as a direct cleavage substrate of caspase‐3, is overexpressed in many epithelial cancers. The N‐terminal‐truncated RhoGDIβ (ΔN‐RhoGDIβ) is accumulated in caspase‐3‐activated cells. Stable expression of ΔN‐RhoGDIβ in HeLa cells did not induce apoptosis, but impaired directional cell migration in a wound‐healing assay accompanied by a perturbed direction of cell division at the wound edge. Subcellular protein fractionation experiments revealed that ΔN‐RhoGDIβ but not wild‐type RhoGDIβ was present in the detergent‐soluble cytoplasmic and nuclear fractions and preferentially associated with Cdc42. Furthermore, Cdc42 activity was constitutively inhibited by stable expression of ΔN‐RhoGDIβ, resulting in increased radiation‐induced compensatory proliferation linking to RhoA activation. Thus, ΔN‐RhoGDIβ dominant‐negatively regulates Cdc42 activity and contributes to loss of polarity‐related functions. The caspase‐3‐cleaved RhoGDIβ is a possible determinant to promote cancer spreading due to deregulation of directional organization of tumor cell population and inhibition of default equilibrium between proliferation and apoptosis after cytotoxic damage. J. Cell. Physiol. 231: 2493–2505, 2016. © 2016 Wiley Periodicals, Inc. Abstract : The N‐terminal‐truncated RhoGDIβ (ΔN‐RhoGDIβ) is accumulated in caspase‐3‐activated cells. ΔN‐RhoGDIβ dominant‐negatively regulates Cdc42 activity and contributes to loss of polarity‐related functions. ΔN‐RhoGDIβ is a possible determinant to promote cancer spreading due to deregulation of directional organization of tumor cell population and inhibition of default equilibrium between proliferation and apoptosis after cytotoxic damage.